Breath on the mirror : mythic voices & visions of the living Maya - Tedlock, Dennis, 1939-2016 (HarperSanFrancisco, 1994)
This remarkable book lets readers hear Maya myths as they are told today in the mountains of Guatemala. First published in 1993, Breath on the Mirror is now available only from UNM Press. "A fascinating literary and anthropological excursion into the mental universe of the modern Quiche Maya and their forebears. The stories and myths so compellingly recounted here turn our own world upside-down and remake it in the Maya image. Reading this, one can understand why and how Maya culture has survived five centuries of oppression."--Michael D. Coe, Yale University, author of The Maya